Water cycle geo facts - Amson-Bradshaw, Georgia (Geofacts (Crabtree Publishing Company), 2018)
Examines the water cycle in all forms, from evaporation to ice. Profiles a number of locations across the world with unique water situations, such as the Amazon rainforest and the polar ice caps. Includes a glossary, text-related questions with an answer key, resources for further information, diagrams, maps, and color photographs.